2014
DOI: 10.1186/2045-3329-4-11
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of published studies involving systemic treatment for chondrosarcoma of bone between 2000 and 2013

Abstract: BackgroundThe majority of patients with chondrosarcoma of bone have an excellent overall survival after local therapy. However, in case of unresectable locally advanced or metastatic disease the outcome is poor and limited treatment options exist. Therefore we conducted a survey of clinical phase I or II trials and retrospective studies that described systemic therapy for chondrosarcoma patients.Materials and methodsUsing PubMed, clinicaltrials.gov, the Cochrane controlled trial register and American Society o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 49 publications
0
20
0
1
Order By: Relevance
“…anthracyclineand gemcitabine-based combinations, ifosfamide, cisplatin. 6,7 With conventional cytotoxic chemotherapy, RECIST disease stabilisations are more commonly observed than objective responses. In the largest retrospective series, published by Italiano et al, cumulative objective response rate (ORR) was significantly dependant on the histotype, being 11% for conventional chondrosarcoma, with a median progression-free survival (PFS) of 5 months.…”
Section: Chondrosarcomamentioning
confidence: 99%
See 1 more Smart Citation
“…anthracyclineand gemcitabine-based combinations, ifosfamide, cisplatin. 6,7 With conventional cytotoxic chemotherapy, RECIST disease stabilisations are more commonly observed than objective responses. In the largest retrospective series, published by Italiano et al, cumulative objective response rate (ORR) was significantly dependant on the histotype, being 11% for conventional chondrosarcoma, with a median progression-free survival (PFS) of 5 months.…”
Section: Chondrosarcomamentioning
confidence: 99%
“…7 Probably, molecular heterogeneity and different pathogenetic mechanisms within different chondrosarcoma variants complicate this issue. 11 The initial enthusiasm driven by pre-clinical data with Hedgehog pathway inhibitors has been frustrated after results of a Phase 2 study in which no objective responses were observed.…”
Section: Chondrosarcomamentioning
confidence: 99%
“…The current standard therapy for chondrosarcoma is surgery. There is no evidence for a benefit of (adjuvant) radiotherapy or chemotherapy, as chondrosarcoma is considered to be highly therapy resistant 7. Consequently, the 1-year survival rate of metastasised high-grade chondrosarcoma is <10% 8.…”
Section: Introductionmentioning
confidence: 99%
“…There is no evidence for a benefit of (adjuvant) radiotherapy or chemotherapy, as chondrosarcoma is considered to be highly therapy resistant. 7 Consequently, the 1-year survival rate of metastasised high-grade chondrosarcoma is <10%. 8 Gliomas vary from WHO grade II diffuse astrocytoma and diffuse oligodendroglioma, with median survivals of more than 5 years, 9 to WHO grade IV glioblastoma, with a median survival of only 15 months despite aggressive treatment using radiotherapy and temozolomide.…”
Section: Introductionmentioning
confidence: 99%
“…Surgery is the cornerstone of the primary management of chondrosarcoma. The current treatment options for patients with unresectable or metastasized disease are limited as chondrosarcomas are relatively chemotherapy-resistant and radiotherapy-resistant [9,10]. The outcome of unresectable conventional chondrosarcoma is 48% at 1 year and 2% at 5 years [11 & ].…”
Section: Introductionmentioning
confidence: 99%